Kesesuaian Zonasi Pulau-Pulau Kecil : Studi Kasus Kawasan Konservasi Gili Sulat Gili Lawang Lombok Indonesia - Sitti Hilyana; Sadikin Amir; Saptono Waspodo (LPPM Universitas Mataram, 2020)
Gili Sulat Gili Lawang are small islands that have high marine biodiversity and have been designated as a Marine Tourism Park (TWP) covering an area of 10,000 hectares. This study aims to analyze the suitability of zoning and analysis of space use in each zone. The data was collected by using a structured interview technique using a questionnaire and Focus Group Discussion (FGD) approach. Zoning suitability analysis used a Geographic Information System (GIS). The assessment showed that the conditions of the mangrove ecosystem, coral reef ecosystem and seagrass ecosystem were in the bad to good categories. Based on the zoning suitability analysis of 193.83 hectares (44.02%) of the coral reef area suitable for the core zone, 143.33 hectares (32.55%) consists of 108 hectares of coral reef ecosystems and 35.43 hectares of seagrass ecosystems suitable for the zone. limited use, and 9,666.47 hectares are suitable for other zones consisting of a coral reef rehabilitation zone covering an area of 93.11 hectares, a protection zone of 93.11 hectares and other waters 8,585.76 hectares.